الطرق العلمية في تحديد الإحتياجات التدريبية وعلاقتها بجودة أداء العاملين في المنشأة الرياضية: دراسة ميدانية لعاملين بالمركبات الرياضية الولائية بالجنوب الجزائري - محمد، بعيط عيسى Mohammed, Bait Isa; مخلوف، حمادى جمال Makhlouf, Hamady Gamal; عبدالقادر، الحاج عيسى رفيق Abdulqader, Haj Issa Rafiq (جامعة حلوان - كلية التربية الرياضية للبنين, 2017)
The study aims to know the extent in using scientific methods in determininig training need and its relationship with performance qualitu of the personnels inside the sports institutions Research problematical: Is ther any connectivity relationship between using scientific methods in determining training need and the performance quality of staff inside districts sports complexes in the south of algearia? Research thesis: Tere is connectivity relationship between using scientific methods in determining training need and the quality of performance of the staff inside districte sports complexes in the south of algeria Methodology used in the study: we relied on the connecting descriptive methodology in our study. Group and pattern of the research: the research group in our study is all the employees in districts sports compleexes in the south of algeria but the pattern has been selected using the random probabilistic method . Means of data collection : A from with the metthod of leckert that measures the scientific methods in determining training need -Aform with the method of leckert that measures the quality of performance of staff . Statistical treatment : we used the calculation averages and normativeness variation connectivity coefficient of learson and mono direction disparity analyse. Research results : -Ther is a connectivity relationship between using scienthfic methods in determining training needs and the performance quality of the personnels in sports institution in the districts sports complexes in southern algeria. -Ther are moral differences in the level of determining training needs and the quality of performance of staff due to personal and professioneel variations
تهدف الدراسة إلى التعرف لمدى استخدام الطرق العلمية في تحديد الإحتياجات التدريبية وعلاقتها بجودة أداء العاملين داخل المنشأة الرياضية. إشكالية البحث: هل توجد علاقة إرتباطية بين استخدام الطرق العلمية في تحديد الإحتياجات التدريبية وجودة أداء العاملين داخل المنشأة الرياضية للعاملين داخل المنشأة الرياضية للعاملين بالمركبات الرياضية الولائية بالجنوب الجزائري؟ فرضية البحث: توجد علاقة إرتباطية بين استخدام الطرق العلمية في تحديد الإحتياجات التدريبية وجودة أداء العاملين داخل المنشأة الرياضية للعاملين بالمركبات الرياضية الولائية بالجنوب الجزائري. المنهج المتبع في الدراسة: إعتمدنا في دراستنا على المنهج الوصفي الإرتباطي. مجتمع وعينة البحث: مجتمع البحث في دراستنا جميع العاملين بالمركبات الرياضية الولائية بالجنوب الجزائري. أما عينة البحث تم اختيارها بالطريقة الإحتمالية العشوائية. أدوات جمع البيانات: تم بناء إستمارتان - إستمارة على طريقة ليكرت تقيس الطرق العلمية في تحديد الاحتياجات التدريبية. - إستمارة على طريقة ليكرت تقيس جودة تقييم أداء العاملين. المعالجة الإحصائية: إستخدمنا المتوسط الحسابي والإنحراف المعياري، معامل الإرتباط بيرسون، تحليل التباين أحادي الإتجاه. نتائج البحث: - توجد علاقة إرتباطية بين استخدام الطرق العلمية في تحديد الإحتياجات التدريبية وجودة أداء العاملين في المنشأة الرياضية العاملين بالمركبات الرياضية الولائية بالجنوب الجزائري. - توجد فروق معنوية في مستوي تحديد الإحتياجات التدريبية وجودة أداء العاملين تعزي للمتغيرات الشخصية والمهنية
Keywords: التدريب المهني -- إدارة الموارد البشرية -- تقييم الأداء -- المؤسسات الرياضية -- الجزائر